2006
DOI: 10.1088/0741-3335/48/5a/s47
|View full text |Cite
|
Sign up to set email alerts
|

Scaling of density peaking in JET H-modes and implications for ITER

Abstract: Abstract:Results from an extensive profile database analysis of JET density profiles in H-mode, show that the density peaking factor n e0 / in JET H-modes increases as the effective collisionality ν eff ≈10 −14 RZ eff n e /T e 2 drops from ~1 at mid-radius to below 0.1 as expected for ITER. Density peaking is also strongly correlated with the Greenwald number N G , the particle outward flux Γ from the neutral beam source and T i /T e . The correlations with l i , q 95 , β N , ρ*, L Te , L Ti , the toroid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

23
94
2

Year Published

2007
2007
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 55 publications
(119 citation statements)
references
References 14 publications
23
94
2
Order By: Relevance
“…On the other hand, it has been reported that the density becomes peaked with the decrease of collisionality [20]. In the ITER plasma, the collisionality will be much lower than the present plasmas and n e edge cannot rapidly increase compared with n e .…”
Section: Individual Density Dependencementioning
confidence: 68%
“…On the other hand, it has been reported that the density becomes peaked with the decrease of collisionality [20]. In the ITER plasma, the collisionality will be much lower than the present plasmas and n e edge cannot rapidly increase compared with n e .…”
Section: Individual Density Dependencementioning
confidence: 68%
“…This definition differs from the one used in previous publications [3,4], * = RS NBI /n e χ, where χ is the heat diffusivity. The definition adopted here makes the comparison with simulations straightforward, as explained later.…”
Section: Introductionmentioning
confidence: 93%
“…It is usually difficult to separate the effect of density from the effect of the collisionality due to its co-linear behaviour [31]. However, careful analysis suggests the presence of an anomalous pinch leading to density peaking, which could increase the fusion power in ITER by almost 30% [31]. Figure 10 suggests a density peaking with decreasing collisionality; however figure 11 suggests that the density peaking is more related to the normalized density (and maybe underlying effects of core fuelling versus edge fuelling).…”
Section: Profile Peakingmentioning
confidence: 99%
“…The stronger correlation with the normalized density can result from the strong gas fuelling in those type-III ELMy H-mode discharges. Investigations on the density peaking are usually restricted to type-I ELMy H-modes without gas fuelling [31] and even the neutral beam fuelling is reduced to avoid any ambiguity in the determination of the inward pinch velocity resulting from particle sources [30]. However, the plasma core in type-I ELMy H-modes and type-III ELMy H-modes should behave similarly.…”
Section: Profile Peakingmentioning
confidence: 99%